PENERAPAN MODEL PEMBELAJARAN AUDITORY, INTELLECTUALY DAN REPETITION (AIR) DENGAN MENGGUNAKAN MEDIA PEMBELAJARAN KARTU ARISAN UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA KELAS X MIA 1 SMAN 8 KOTA BENGKULU - Diana Sumiati; Amrul Bahar; Dewi Handayani (ALOTROP, 2019)
This study aimed to improve learning activities and learning outcomes of students in class X MIA 1 of Senior High School (SMAN) 8 Bengkulu on the subject of chemical bonds through the application of Auditory, Intellectualy, and Repetition (AIR) learning models by using learning media with lottery card. This study is a classroom action research consisting of three cycles, each cycle consisting of four stages, planning, action, observation and reflection. In collection of data was done by non-test and test methods, teacher observation sheets, student observation sheets and post-test. The data was processed by using simple quantitative data analysis techniques, the total value of each student, the average value, the percentage of absorptive power, learning completeness and the average observation score.The results of the study in the 2018/2019 school year showed that the application of the Auditory Intellectualy Repitition learning model using learning media with lottery  cards in class X MIA 1 of SMA Negeri 8 Kota Bengkulu could improve teacher activities, student activities and student chemistry learning outcomes. This can be seen from the average score of teacher activities in the first cycle to the third cycle in a row : 23, 27.5 and 31.5. Student activity also showed improvement in each cycle. The average score of student activity in cycle I to cycle III was sequentially 20, 25 29.5. Learning outcomes also increase in each cycle. This can be seen from the average value of the test results in each cycle, in the first cycle of 61.82, in the second cycle of 67.88, in the third cycle of 79.09. Classical absorption in cycle I, cycle II, cycle III are 61.82%, 67.88%, 79.09%, with the percentage of completeness learning in each cycle of 42%, 73%, and 87.8 %.